2016
DOI: 10.2320/matertrans.m2015358
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Arrangement and Magnetic Order in Mn<sub>2</sub>RuZ (Z = Sn, Si)

Abstract: Recently, new compounds Mn 2 RuSn and Mn 2 RuSi were synthesized and their crystal structures were studied by X-ray diffraction measurements. This measurement indicates that they have a Heusler-like cubic structure, but the details have been unclear so far. To clarify their atomic arrangement and magnetic order, we carried out first-principles total-energy calculations for several different atomic arrangements, together with ferrimagnetic and ferromagnetic ordering. The comparison among total energies indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Previous first-principles studies suggest nearly halfmetallic electronic structure in their bulk form. [25][26][27][28][29] In the spin-dependent transport properties of MTJ with Heusler-alloy electrodes and single crystalline MgO barrier, the presence of spin-polarized ∆ 1 -band for the Heusler alloy plays an important role. [32] Therefore, before studying the Heusler-alloy/MgO (001) heterojuntion, it is of extreme interest to discuss the symmetry of the bands crossing the E F along the ∆ axis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous first-principles studies suggest nearly halfmetallic electronic structure in their bulk form. [25][26][27][28][29] In the spin-dependent transport properties of MTJ with Heusler-alloy electrodes and single crystalline MgO barrier, the presence of spin-polarized ∆ 1 -band for the Heusler alloy plays an important role. [32] Therefore, before studying the Heusler-alloy/MgO (001) heterojuntion, it is of extreme interest to discuss the symmetry of the bands crossing the E F along the ∆ axis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous first-principles studies suggest nearly halfmetallic electronic structure in their bulk form. [25][26][27][28][29] These motivate us to investigate the Mn 2 RuZ/MgO (001) heterostructures. Endo et al [30] first reported Mn 2 RuSi to have spinglass like magnetic structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The site preference, electronic structure and magnetism of the Mn 2 RuSn Heusler compound have been investigated using theoretical calculations (Chen et al, 2014;Yang et al, 2015;Shimosakaida & Fujii, 2016). The XA-type structure was confirmed to be the most stable structure in Mn 2 RuSn and the moments of the two Mn atoms in the cell are in antiparallel alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Among Mn 2 YZ full‐Heusler compounds, Mn 2 VAl was first predicted by first‐principles calculations to be a half‐metallic ferrimagnet [5]. Since then, the half‐metallic ferrimagnetism was observed in the electronic structures of many Mn 2 ‐based compounds from first‐principles calculations [6–20]. However, the investigations on Mn 2 NbZ are rare to the best knowledge of the authors.…”
Section: Introductionmentioning
confidence: 99%